APPLICATION OF DISCOVERY LEARNING LEARNING MODEL IN IMPROVING ENGLISH LEARNING OUTCOMES IN GRADE VIII B STUDENTS OF MTS ISLAMIYAH SUKOPURO - krisnawati, krisnawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The purpose of this study was to determine whether there was a student response of the effect of the application of the Discovery Learning models in improving English learning outcomes in the daily test of class VIII B MTs Islamiyah Sukopuro. This type of search in classroom action research which is conducted face-to-face offline in the classroom. The subjects of this study were class students VIII B Islamiyah Sukopuro add smester for the academic year 2022-2023. The object of this research is the results of daily tests. This study uses two cycles to improve the abilityto analyze the results of daily tests through four stages of activities, namely planning, action, evaluation, and reflection. The collection technique in this study used the test and observation method. The results showed that 1 the application of the Discovery Learning model was able to improve students’ ability to understand the material. 2the results of students responses to the application of the Discovery Learning model were quite successful, especially when viewed from the results of daily tests in understanding the material.